INCORPORATING DRAMA IN ENGLISH CLASSROOM - Syafrina Prihatini (English Education Study Program FKIP Universitas Alwashliyah Medan, 2022)
This article attempts to describe using drama to teach students of English classroom. Drama can be one source and effective way to assist students learns English. It uses active teaching and learning activities in the classroom which are likely can motivate and engage the attention of the students. Teaching English using drama is not easy. Drama classroom activities can include role-play, drama games, improvisation, group discussion and individual or pair work. Therefore, teaching English using drama needs serious attention from the lecturer. This article focuses on how to teach English with drama. It is expected that this strategy will give significant improvement on students’ achievement in mastering English language skills.